Evaluación de la asimilación de competencias no académicas dentro de un programa de postgrado en una universidad de Colombia con técnicas de minería de datos (2020)
Postgraduate programs, especially in Engineering and Management, prepare professionals to assume collaboration, resolution, planning and leadership tasks in organizations, turning them into entities that facilitate change and integrators of engineering, administration and technologies, through the application of knowledge, methodologies and tools for the modeling, design and administration of complex systems that involve people, processes, technologies and information and that are oriented both to the achievement of organizational objectives and to innovation and entrepreneurship with an ethical sense and social responsibility. In this context, postgraduate programs deepen the need to implement or reinforce within their courses, "non-academic" competencies in order to balance the technical and academic teachings of each program with softer competencies, seeking to obtain a combination of competencies. Global profiles for more comprehensive profiles that can interact more effectively within organizations. In this work, the evaluation of soft skills was approached with a focus on their temporary assimilation among 80 professionals who participated in the Master's program in Engineering Management at the Universidad de la Sábana (Colombia). For this, a methodological / experimental framework was proposed in the context of KDD (Knowledge Discovery in Databases) with data mining techniques in order to find assimilation profiles of soft skills through clustering during and after one year of completion of studies , as well as, its possible temporary transition in said temporary moments. Four experiments were carried out in this regard and, using post-processing techniques (group centroids and visualization), findings were obtained that offer the evaluative status at the grouped level of the assimilation of soft skills in the case study. The soft skills studied are: Planning, Reaching, Acting, Adaptability, Motivation and Leadership, which appeared in general reinforced lines after one year of the completion of studies. The results obtained, in addition to measuring the degree of assimilation of said competencies and their change or transition after one year, open the way to support decisions or possible changes in the reinforcement or maintenance of current internal practices within the evaluated master's program. Finally, this research offers future lines of research to initiate more exhaustive, reverse-engineered and predictive analyzes when more data can be counted on.